Desarrollo Del Pensamiento Contable A Traves De Las Mediaciones Semióticas E Iteracciones Con Los Modelos Matematicos (Global Journal of Management and Business Research, 2019)
Abstract not found
Keywords: interest rate spread; commercial banks.